Karakteristik Pasien Gagal Jantung di Poliklinik Jantung RSUD Dr. M. Haulussy Kota Ambon Maret 2022 - Haikal Eko Fahrianto Rahawarin; Irwan Irwan; Denny Jolanda (Lembaga Pengembangan Kinerja Dosen, 2025)
Heart failure is a major cause of morbidity and mortality worldwide. Based on data from the World Health Organization (WHO), one of the most non-communicable diseases in the world is cardiovascular disease, whose spectrum is heart failure. To diagnose heart failure, a clinical history, physical examination and investigations are required. This study aims to determine the characteristics of heart failure patients at the heart polyclinic of RSUD Dr. M. Haulussy Ambon City March 2022. This research is a descriptive study. The number of samples in the study was determined using a categorical descriptive formula and the samples were taken using a simple consecutiv sampling technique. The data obtained were analyzed using the Statistical Package for the Social Science (SPSS). The results showed that from 74 samples of heart failure patients, 37 people aged >60 years (50%), 42 men (56.8%), 55 people had a history of coronary heart disease (74.3%). , as many as 21 people had a history of hypertension grade 1 (35.1%), as many as 7 people had a history of diabetes mellitus (9.5%), as many as 27 people took diuretic drugs (36.5%), as many as 34 people had a history of smoking (45.9%), as many as 31 people had a history of hospitalization (41.9%), as many as 26 people had a history of arrhythmias (35.1%), as many as 8 people had a history of valve abnormalities (10.8%).